A new species of Miogryllus Saussure, 1877 from Andean Venezuela with bizarre cephalic morphology (Orthoptera, Gryllidae, Gryllinae, Modicogryllini) - de A. G. De Mello, Francisco; Morselli, João Paulo (Zootaxa, 2011)
Miogryllus muranyi n. sp. is described from the Andean Acacia-Cactaceae semi-desert bush in the Chama Valley of Venezuela. The species is characterized by the unusual shape of the male head, which makes it readily distinguishable from any other congener known to date.